Effect of Trilostane on Hormone and Serum Electrolyte Concentrations in Dogs with Pituitary‐Dependent Hyperadrenocorticism. (16th December 2013) - Griebsch, C.; Lehnert, C.; Williams, G.J.; Failing, K.; Neiger, R.
<x xml:space="preserve">Abstract</x> Background The effects of trilostane on key hormones and electrolytes over 24 hours in dogs with pituitary‐dependent hyperadrenocorticism (PDH) are unknown. Objectives To determine the plasma concentration of cortisol, endogenous adrenocorticotropic hormone (ACTH), aldosterone, sodium, potassium, and ionized calcium concentrations, and plasma renin activity over a 24‐hour period after administration of trilostane to dogs with well‐controlled PDH. Animals Nine dogs (mean age 9.3 ± 0.67 years, mean weight 31.9 ± 6.4 kg) with confirmed PDH. Methods Prospective study. Thirty days after the first administration of trilostane, blood samples were taken at −30, 0 (baseline), 15, 30, 60, and 90 minutes, and 2, 3, 4, 6, 8, 12, 16, 20, and 24 hours after administration of trilostane and plasma concentration of cortisol, endogenous ACTH, aldosterone, sodium, potassium, ionized calcium, and renin activity were determined. Results Cortisol concentrations decreased significantly (P < .001) 2–4 hours after trilostane administration. From baseline, there was a significant (P < .001) increase in endogenous ACTH concentrations between hours 3–12, a significant increase (P < .001) in aldosterone concentration between hours 16–20, and a significant (P < .001) increase in renin activity between hours 6–20. Potassium concentration decreased significantly (P < .05) between hours 0.5–2. Conclusion and Clinical Importance Treatment with trilostane did not cause clinically relevant alterations in plasma aldosterone and potassium concentration. Results suggest that in dogs with PDH, the optimal time point for an ACTH‐stimulation test to be performed is 2–4 hours after trilostane dosing. Future studies are necessary to establish interpretation criteria for a 2‐ to 4‐hour postpill ACTH‐stimulation test.